Stability in BMI over time is associated with a better cognitive trajectory in older adults. (31st December 2021) - Beeri, Michal Schnaider; Tirosh, Amir; Lin, HungMo; Golan, Sapir; Boccara, Ethel; Sano, Mary; Zhu, Carolyn W
Abstract: Background: Despite the relevance of body mass index (BMI) to the risk of incident cognitive impairments and the subtle but consistent decrease in BMI which accompanies old age, there is limited evidence on the simultaneous changes in BMI and cognitive decline, which better reflect the natural course of both health phenomena. Whether BMI stability contributes to better cognitive trajectories is essentially unknown. To address this gap in knowledge we examined the longitudinal associations of changes in BMI over time with changes in cognition. Method: We exploited longitudinal clinical data from 15, 977 initially non‐demented older adults participating in the Alzheimer's Disease Centers across the United States followed for an average of 5 years. In this longitudinal study, changes in BMI were defined as 1) last minus first BMI, 2) mean of all follow‐up BMIs minus first BMI, and 3) standard deviation (SD‐representing variability) of BMI change from baseline and all follow‐up visits. Linear mixed effect models assessed the association of each of the BMI change variables with cognitive decline, adjusting for a broad range of sociodemographic, cardiovascular, and functional measures. Result: Participants averaged 73.5 (7.6) years of age and 15.6 (3.6) years of education; 59.2% were women and 80.9% Caucasians. Participants who had significant changes in BMI defined as an increase or decrease of > 5% in BMI, or who had greater variability in BMI, had a faster rate of cognitive decline in global cognition and the specific cognitive domains. Furthermore, this pattern was consistent irrespective of whether a person had normal (BMI<25; N= 5747), overweight (BMI=25 to 29.99; N=6302), or obese (BMI>30; N=3928) BMI at baseline. Conclusion: Our study provides new evidence that greater changes (or variability) in BMI over time are associated with a faster rate of cognitive decline suggesting that in initially non‐demented older adults, stability in BMI predicts a better cognitive trajectory. These results suggest a potential clinical value in tracking BMI change, which is simple to measure, as it may point to individuals whose cognition is declining.